1999
DOI: 10.1108/02602289910266287
|View full text |Cite
|
Sign up to set email alerts
|

Combining inorganic and organic gas sensors elements: a new approach for multi‐component sensing

Abstract: Atmospheric dependent, gas sensitive resistors seem to be good candidates for detecting critical air pollution levels. Recently, great progress has been made in the development of various sensor types, but less attention seems to be paid to the integration of sensor elements with different characteristics. The aim of this international project is to develop a smart hybrid gas multisensor module for environmental applications, i.e. by combining classical thick-and thin-film elements with polymer-film based sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The researchers suggested that nanocomposites are useful in optoelectronic devices . The PVA composite materials could be utilized in different types of sensors including mechanical, chemical, and biological ones .…”
Section: Physics Of Pvamentioning
confidence: 99%
“…The researchers suggested that nanocomposites are useful in optoelectronic devices . The PVA composite materials could be utilized in different types of sensors including mechanical, chemical, and biological ones .…”
Section: Physics Of Pvamentioning
confidence: 99%
“…Polyaniline and polypyrrole have successfully been applied in multicomponent gas sensing. Their advantages over inorganic gas sensor materials are their high selectivity and the ability to operate at ambient temperatures, without the necessity of heating [26].…”
Section: Electroconducting Conjugated Polymersmentioning
confidence: 99%
“…Use of the molecular organic crystals opens wide possibilities for formation of sensitive architectures with predefined chemical functionality. Characteristic examples of this approach are given by the use of various cavitands, first of all calixarenes [12][13][14], which are very promising materials considering the possibility of optimization of their structure to match the analyte molecules' one [15][16][17][18][19][20]. These peculiarities of the molecular structure (presence of the nanocavities) and also the ability of molecular recognition of the organic compounds allow to utilize the calixarenes for creation of the gas sensors sensitive layers [21].…”
Section: Introductionmentioning
confidence: 99%